Manajemen Kepala Sekolah Dalam Meningkatkan Mutu Pendidikan Sekolah Menengah Kejuruan Negeri 15 Samarinda - Sri Hartono; Husniah Achmad (Sekolah Tinggi Agama Islam An-Nawawi Purworejo, 2021)
This study aimed to discuss the principal management in improving the quality of education at SMKN 15 Samarinda. There are three things raised in this study: firstly, the principal's role, secondly the obstacle faced by the principal, and thirdly the principal's effort in improving the quality of education. This research uses descriptive qualitative analytical design, and it was conducted from February to August 2021 at SMK Negeri 15 Samarinda Jl. Ir. H. Nusyirwan Ismail, M.Si, Lok Bahu, Kec. Sungai Kunjang, Samarinda, East Kalimantan. There are two types of data in this study: primary data obtained from observations and interviews and secondary data obtained from documentation during this research. Data validation is done through a triangulation process. Data analysis techniques used in this research are reduction, verification of presentation, and drawing of conclusions. The results showed that the principal management is done by system embodied at SMKN 15 Samarinda in the implementation of education. The principal appears as a educator, manager, administrator and supervisor figure who guides teachers and students so that the educational goals at the SMKN 15 Samarinda can be achieved properly. The principal's leadership binds and harmonizes and encourages all potential school resources for improving the quality of education.